Cases on applying knowledge economy principles for economic growth in developing nations - Piaggesi, Danilo, 1956-; Landázuri, Helena; Jia, Bo, 1996- (Advances in finance, accounting, and economics (AFAE) book series., 2022)
"The goal of the book is a variety of perspectives on the conditions under which the Knowledge Economy concept -and the triple helix approach-- are of value for developing countries, and which adaptations are being applied to adjust to local circumstances"--